Perbedaan Pemikiran Islam Klasik, Pertengahan, dan Modern serta Perkembangannya - Kristianto, Davit; Alimni; Ismail (INSTITUT AGAMA ISLAM TARBIYATUT THOLABAH LAMONGAN, INDONESIA, 2023)
The development of Islamic thought and civilization was supported by caliphs who loved science with maximum facilities and funds, established political and economic stability. This is in line with the high enthusiasm of Muslim scholars and intellectuals in carrying out the development of religious, humanities and exact sciences through the movement of research, translation and writing scientific papers in various scientific fields. Then their real work movement in the field of artifact civilization. In the era of jahiliyah, there had been tremendous damage to aqidah and morals in Mecca. Damage such as drunkenness, robbery, and worship other than Allah. In overcoming the problem, Allah SWT. sent the Prophet Muhammad SAW to repair the aqidah and morals that had been damaged in Mecca. The first step taken by the Prophet Muhammad SAW. namely teaching monotheism to the people in Mecca, but when the Prophet was 63 years old he died and at that time he still did not succeed in improving the aqidah and morals of the people of Mecca. Shortly after the death of the Prophet the companions decided to deliberate consensus, namely to elect a successor to the Prophet Muhammad SAW. The first successor was Abu Bakar as-Siddiq, Umar Bin Khattab, Usman bin Affan, and finally Ali bin abi Talib. These companions are called Khulafaur Rashiddin. Thought in Islam was born long after the emergence of Islam, after going through a long historical process. At least modern thought in Islam among thinkers emerged after Islam experienced a period of decline in all fields since the fall of the caliphate of Abbasid bani in Baghdad in 1258 AD. Thought is divided into three periods: Classical Islamic thought, Medieval Islamic thought, and Modern Islamic thought.